A questão regional no Nordeste: Uma análise da trajetória socioeconômica do Nordeste brasileiro entre a década de 1950 e o final dos anos 2000 - Gonçalves, Hugo Feitosa (2016)
The Northeast throughout its history was presented as a heterogeneous region, which could be divided into several Northeasts. This region which is homogenised by the characterization of the drought, the traditionalism in your production system, poverty and various stereotypes. With the analytical perspective the socio-economic situation of the Northeastern population encompassed in the national scene, this research has the general objective to verify the socio-economic trajectory of the Northeastern population between the 1950s and the late 2000s; the specific objectives then seek to answer the following questions: which political and socioeconomic scenarios met the Northeast in its historical trajectory from the "Regional Issues" in the Northeast in the 1950s? What is the economic and social situation of the region in the late 2000s? What factors - political, economic, etc. - They were part of the formation of the Northeast characteristic between the second part of the twentieth century and the first decade of this century? This work has as its theme and cut periodic socio-economic trajectory of the Northeast between the 1950s and 2000s; the spatial area is the political and administrative area demarcated by the Federal Government of the Northeast. The research has a descriptive character, with a text presented qualitative and quantitative, and research based on bibliographies and documents due to spatial and periodic amplitude analysis, and quantitative factors presented to outline the general economic and social conditions in the Northeast in recent years , with the comparative reference numbers presented by Brazil in general. Research shows that the outbreak of the "Regional Issues" in the Northeast in the 50s, this region was the poorest in the country, there was a wide disparity of income among the northeastern population and the Southeast, as well as concentration of income in the Northeast, which it was an aggravating factor. With the regional planning voted for the Northeast and the exploitation of natural resources in the military government, the product of this region is growing at a level above the national, but the concentration of income increased further in the Region; the Northeast had the worst social indicators, distancing increasingly the national average. In the FHC governments, the GDP of the region grows less than the national average, losing ground in the composition of the Brazilian product. Despite the income of the Northeast have increased, leaving less distant from the level of income of the inhabitants of the Southeast, between 50 and 90, the per capita GDP and income concentration in the Northeast still had the worst indicators in the country. Poverty despite be minimized, the region still harbored the largest number of poor people; the illiteracy rate was double the national average and other indicators also analyzed were below the average for Brazil. In Lula governments, the GDP of the Northeast grows more than the country; the income of the Northeast increases more than the national average, but in 2010 the income of the Northeast was still the lowest among the regions. Poverty, even being minimized in the region, it continues to host the largest number of poor. Inequality of income and the illiteracy rate worsened even more than the national average and the other variables were closer to the national average. At the end of Lula governments, illiteracy, poverty and income concentration were still important issues in the Northeast.